Reflection and refrection of electromagnetic waves at the boundary of anisotropic media of monocline symmetry - Тлеукенов, С. К.; Жалгасбекова , З. К.; Балабеков, К. Н. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The indicatrices of the wave vector, phase and group velocities of the electromagnetic waves TE and TM polarization in monoclinic crystals are obtained for nonzero εyz and µyz - elements of the dielectric and magnetic permeability tensors. For the class of monoclinic crystals under consideration, there has been determined existence of two types of TE waves:( Ex , Hy ), ( Ex , Hz ) and two types of TM waves: ( Hx , Ey ), ( Hx , Ez ) propagating in the coordinate plane (yoz) without mutual transformation. Equations of the indicatrix of wave vectors, phase and group velocities have been obtained for all types of waves. The problem of the reflection of TE and TM polarization electromagnetic waves at the boundary of monoclinic crystals of the class under consideration has been solved analytically. The authors have been determined the flux densities of reflected and refracted electromagnetic waves.